Participation: The Happiness Connection - Brian Martin; Chris Barker (Journal of Deliberative Democracy, 2011)
Participation in decision-making has the potential to contribute to greater happiness. To explore this connection, we examine three areas: the family, the workplace and politics. In each of these areas, happiness research suggests that greater participation should increase happiness, most directly via the channels of personal relationships and helping others. There is some empirical research suggesting that participation contributes to happiness. It is useful to consider the connections between the three areas. In particular, examination of participation-happiness connections within families and workplaces can provide some insights for promoting a stronger connection at the level of politics.